Titles framed as questions reduce reader engagement - Fang, David; Wheeler, S. Christian (Journal of Consumer Psychology, 2026)
Abstract People typically read the titles of content (e.g., an article or post) before deciding whether to consume it. Titles can be composed as a statement (e.g., “Green Tea Has Health Benefits”) or a question (e.g., “Does Green Tea Have Health Benefits?”). Question titles are common and are believed by journalists to increase engagement. The present research examines whether this is the case. Four studies—including archival analyses of Reddit posts ( N = 53,030) and academic articles ( N = 3,078,791), online news headline experiments ( N = 22,743 A/B experiments), and a pre‐registered lab study ( N = 400)—indicate that question‐framed titles reduce reader engagement because they are viewed as less informative. These findings suggest that those wishing to maximize engagement with written content should avoid using questions in their titles.